Colorful House of Math logo
Log in

Two Parentheses with Variables


If there are variables in addition to numbers inside of two pairs of parentheses, you can’t find their exact values. There’s a rule to expand these kinds of parentheses, based on the distributive property.

Rule

Product of Parentheses with Variables

= (a + b)(c + d) = a(c + d) + b(c + d) = ac + ad + bc + bd

(a + b)(c + d) = a(c + d) + b(c + d) = ac + ad + bc + bd

Example 1

Expand (y + 2)(4 2x)

Since you don’t know the values of x and y, you need to apply the rule above. According to the rule, you need to multiply y by 4 and 2x, and multiply 2 by 4 and 2x, and add those four products together:

= (y + 2)(4 2x) = y(4 2x) + 2(4 2x) = y × 4 + y × (2x) + 2 × 4 + 2 × (2x)

(y + 2)(4 2x) = y(4 2x) + 2(4 2x) = y × 4 + y × (2x) + 2 × 4 + 2 × (2x)

You then apply the rules for contracting expressions with variables and simplify the expression. That gives you
= y × 4 + y × (2x) + 2 × 4 + 2 × (2x) = 4y 2xy + 8 4x

y × 4 + y × (2x) + 2 × 4 + 2 × (2x) = 4y 2xy + 8 4x.

Besides adjusting the order to put variables alphabetically first, and constant terms at the end, there’s nothing left to do with this expression, because you can’t contract terms with different combinations of variables. The final result is
4x 2xy + 4y + 8

Sometimes, there’s a minus sign in front of the parentheses. In those cases, it’s important to move the minus sign to each of the terms inside the parentheses before expanding. If a term inside the parentheses is negative already, it turns positive, because () × () = +. Positive terms inside the parentheses turn negative, because () × + = . You can also think about the minus sign as having an invisible 1 included, meaning you’re multiplying each of the terms inside the parentheses by 1.

Rule

Minus in Front of Parentheses

(a + b) = a b (a b) = a + b (a + b) = a b (a b) = a + b

(a + b) = a b (a b) = a + b (a + b) = a b (a b) = a + b

Example 2

Expand the expression

2b(a + 1) (2ab + 2b)

The first term in the expression is expanded like this: 2b(a + 1) = 2ba + 2b = 2ab + 2b

The second term has a minus sign in front of the parentheses, and can be expanded by applying the rule above:

(2ab + 2b) = 2ab 2b

Then you have that

= 2b(a + 1) (2ab + b) = 2ab + 2b 2ab 2b = 0

2b(a + 1) (2ab + b) = 2ab + 2b 2ab 2b = 0

Want to know more?Sign UpIt's free!
White arrow pointing to the LeftPrevious entry
Parentheses with Variables
Next entryWhite arrow pointing to the right
Combining the Rules